(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article describes ways to reduce problem loans in commercial banks of the Republic of Uzbekistan. In this article, the analysis of the work being done on the issues of lending and working with problem loans in the banking system and the measures taken within the framework of the legislation have been made, as well as information and some recommendations on ensuring the effective operation of the lending and withdrawal system in the banking sector was also given.